Failure of frusemide to increase production of prostaglandin E2 in human nasal mucosa in vivo. Issue 3 (March 1993) - Mullol, J; Ramis, I; Prat, J; Roselló-Catafau, J; Xaubet, A; Piera, C; Gelpí, E; Picado, C
Abstract : BACKGROUND: It has been suggested that inhaled frusemide protects subjects with asthma against bronchoconstriction by enhancing the synthesis of prostaglandin E2 (PGE2). To evaluate this hypothesis the effect of frusemide on PGE2 production from nasal mucosa was studied. METHODS: Two main arachidonic acid metabolites produced by epithelial cells, PGE2 and 15-hydroxy 5, 8, 11, 13-eicosatetraenoic acid (15-HETE), were measured by radioimmunoassay in nasal secretions obtained by nasal lavages with saline. Eleven healthy volunteers were randomly assigned to two study days, one week apart, in a double blind crossover study. Nasal instillation with three increasing doses of frusemide (5, 10, and 20 mg) or placebo was carried out at intervals of 15 minutes. Nasal lavages were performed immediately before nasal instillations and 15, 30, and 60 minutes after the last instillation. RESULTS: Baseline concentrations of 15-HETE were at least six times higher than PGE2. No differences between frusemide and placebo were detected either on PGE2 or 15-HETE release. CONCLUSIONS: The findings do not support the hypothesis that the antiasthmatic effect of frusemide may be due to increased synthesis of PGE2 or release in the respiratory mucosa.